Early Transcriptional Changes in Feline Herpesvirus-1-Infected Crandell-Rees Feline Kidney Cells - Xiuqing Xiao; Fuqiang Xu; Fan Jia (Veterinary Sciences)
FHV-1 is a highly contagious pathogen that significantly threatens feline health and contributes to rising pet healthcare costs. The mechanisms underlying FHV-1 and host interactions remain poorly understood. For the first time, we conducted a systematic analysis of transcriptomic changes in CRFK cells following FHV-1 infection using RNA-seq. The differentially expressed genes (DEGs) displayed significant associations with cellular components, particularly the chromatin structure. Pathway analysis of the DEGs highlighted key host immune responses, including Toll-like receptors (TLRs), IL-17, TNF, MAPK, and Rap1 signaling pathways. By integrating the RNA-seq and RT-qPCR results, we identified CXCL8, CXCL10, MMP1, MMP9, CSF2, CSF3, CCL20, TLR2, TLR3, TLR4, TNF, and FOS as potentially important genes in the host’s immune response to FHV-1. These findings provide valuable insights into the mechanisms underlying FHV-1 and host interactions.